ANTIBACTERIAL AND PHYTOCHEMICAL STUDIES OF PSIDIUM GUAJAVA LEAF EXTRACT - Agrawal, R. C. (International Journal of Research -GRANTHAALAYAH, 2021)
The phytochemical screening, and anti-bacterial activities of the hydro-methanolic leaves extract of Psidium guajava using standard screening methods such as disc diffusion methods. The secondary metabolites such as alkaloids, phenols , saponins, and tannins were present in Psidium guava extract in phytochemical screening, It also showed dose dependent antibacterial activities against almost all the test organisms. Results denote the antibacterial activity of Psidium guajava leaves extract